Forming of Word in Justin Bieber’s Song Titled “Baby” - M. Haddad Al Qusyoi Ar; Emeliya Sukma Dara Damanik; Rafadila Asty; T Zunita Miha Sy (e-Journal of Linguistics, 2023)
This study aims to analyze the word formation that researchers havefound in the lyrics of Justin Bieber's song entitled Baby. The methodused by the researcher is a qualitative research method, where theresearcher investigates the formation of words in the lyrics of JustinBieber's song entitled Baby. The data is taken from data sources,namely from Justin Bieber song lyrics in the browser. The results of thisstudy are the researchers found five types of forming of words, namelythree words from clipping, six words from compounding, one wordfrom blending, one word from coinage, and one word from inflection inthe lyric of Justin Bieber’s song entitled Baby.